2008
DOI: 10.1177/0363546508322897
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Autologous Chondrocyte Implantation in Patients with Failed Prior Treatment for Articular Cartilage Defect of the Knee

Abstract: Patients with moderate to large chondral lesions with failed prior cartilage treatments can expect sustained and clinically meaningful improvement in pain and function after autologous chondrocyte implantation. The subsequent surgical procedure rate observed in this study (49% overall; 40% related to autologous chondrocyte implantation) appears higher than generally reported after autologous chondrocyte implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(201 citation statements)
references
References 33 publications
6
190
3
1
Order By: Relevance
“…Zaslav et al 67 prospectively followed 154 patients who were treated with an ACI procedure and reported that 77% of patients had good to excellent clinical outcomes based on knee function, knee pain, quality of life, and overall health. Similar prospective studies were completed by Rosenberger et al, 53 who reported that 72% of 56 patients subjectively reported a good to excellent outcome.…”
Section: Restorative Technique: Autologous Chondrocyte Implantationmentioning
confidence: 99%
“…Zaslav et al 67 prospectively followed 154 patients who were treated with an ACI procedure and reported that 77% of patients had good to excellent clinical outcomes based on knee function, knee pain, quality of life, and overall health. Similar prospective studies were completed by Rosenberger et al, 53 who reported that 72% of 56 patients subjectively reported a good to excellent outcome.…”
Section: Restorative Technique: Autologous Chondrocyte Implantationmentioning
confidence: 99%
“…In the early 1990s, Brittberg et al [7] in their initial clinical studies on the effectiveness of ACI, reported good or excellent results in 14 out of 16 patients. Two subsequent clinical trials, conducted in larger groups and longer follow-up terms, showed good-to-excellent results in 76 % [8] and 88 % [9] of patients respectively, indicating that the emerging TE technique would soon replace traditional methods of treatment for cartilage, menisci and ligaments injuries and more suitable cells would be searched for.…”
Section: Cell Sourcesmentioning
confidence: 99%
“…Two studies 30,39 reported the preinjury TAS. The Lysholm scale was applied together with the IKDC Subjective Form in 5 studies, 25,42,43,47,50 but no studies used the Lysholm scale in conjunction with the KOOS. Three studies applied both the IKDC and KOOS.…”
Section: Data Synthesismentioning
confidence: 99%